Lyophilized Human Cord Blood Leukoconcentrate Affects Immune System of Rats with Ischemic Stroke - Lebedynets , Volodymyr; Ostankova, Ludmila; Bondarovych, Mykola; Lebedynets , Dmytro; Ostankov, Maksym; Lutsenko, Olena; Grisha , Igor; Goltsev, Anatoliy (Problems of Cryobiology and Cryomedicine, 2023)
Cerebrovascular pathology, especially acute cerebrovascular accident is among the most complicated issues in medicine. Therefore, the search for efficient ways to treat neurodegenerative diseases has still remained topical. In experimental model of ischemic stroke (IS), the impact of lyophilized and cryopreserved human cord blood leukoconcentrate (lHCBL and cHCBL, respectively) on immune system humoral and cell components has been comparatively studied. The ischemic stroke was simulated in 6-monthold Wistar rats by occlusion of the middle cerebral artery. The lHCBL and cHCBL were administered intraperitoneally at a dose of 0.5 ml of 5 × 106 cells in 6 hrs after surgery (occlusion). In blood serum, the populations and subpopulations of lymphocytes (CD3+, CD4+, CD8+, CD16+, CD4+CD25+), the content of total immunoglobulins and circulating immune complexes were determined. The experimental model of IS showed both lyophilization and cryopreservation of HCBL to ensure the preservation of immunomodulatory potential of cells, that was confirmed in vivo. An equivalent corrective effect of lHCBL and cHCBL on indices of immune system cell and humoral components during IS development has been established. The inclusion of lHCBL, as well as cHCBL and native HCBL in basic therapy of IS promoted a more rapid recovery of the immune system indices in animals. Probl Cryobiol Cryomed 2022; 32(4):277–291